Mediating role of Perceived Strategic Value between Technological Factors and E-Commerce Adoption intentions in SMEs in United Arab Emirates - Alzaabi, Mohammed Obaid Hamad Kaabous; Omar, Rusdi bin; Romle, Abd. Rahim Bin (South Asian Journal of Social Sciences and Humanities, 2021)
The purpose of the study was to identify the mediating role of perceived strategic value between technological factors and e-commerce adoption intentions among Small and medium enterprises operating in United Arab Emirates. For the said purpose critical review of the literature was conducted to develop the framework for empirical testing. The data was collected from the middle top and lower-level employees and the owners. A questionnaire was used as an instrument to collect the data, the instrument was adopted based on previous studies. The results of structural equation modeling confirmed the framework of the study and ensured that perceived strategic value significantly and positively mediates the relationship between technological factors and e-commerce adoption intentions. The future researchers are guided to conduct longitudinal studies to find the long-term effect.